(untitled) (Islamic Sciences Journal, 2023)
Praise be to Allah Almighty ,the Lord of the world, and peace and blessings be upon the faithful Prophet who is sent as a mercy to the world, our Prophet Muhammad, his family and all his companions. This research which is entitled (ALMARWIYAT ALTAFSIRIA ALWARIDA FI SURAT AL’ARAF FI ALJAMIE ALSAHIH "SUNAN ALTRMIDHY" D. (279AH) JAM’AN WA DIRASA) to show the most important prophetic traditions mentioned by Imam Tirmidhi in his interpretation of Sura Al A’raf, through which one can understand the interpretation of the verses correctly. Four traditions have been mentioned in this research which were mentioned only by imam Al-Tirmidhi in the interpretation of some verses from Surat A-A’raf, where a tradition about the interpretation of the story of Moses (PBUH) is mentioned , when he asked Allah Almighty to let him see Him without a veil. This research has dealt also with several hadiths through which Allah Almighty testifies that He is their creator, , their sustainer, and that all human beings are descendants of Adam, peace be upon him. The research is concluded with a set of results and recommendations.